2004
DOI: 10.1089/jmf.2004.7.309
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Bovine Milk Whey Protein Concentrate on the Ulcerative Lesions Caused by Subcutaneous Administration of Indomethacin

Abstract: The protective effect of a whey protein concentrate (WPC) was studied in three models of stomach ulcerative lesions induction: subcutaneous injection of indomethacin, and stress induced by either intraperitoneal injection of reserpine, or immobilization and holding in the cold (4 degrees C, 2 hours). Adult Wistar rats (300-400 g) were used for acute (single-dose), repetitive, or subchronic (10 days) administration of WPC prior to treatment with the ulcerogenic factors. The best protection was achieved in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 8 publications
0
12
1
2
Order By: Relevance
“…Studies reported recently (Rosaneli, Bighetti, Antoˆnio, Carvalho, & Sgarbieri, 2002, 2004) with a WPC produced in a pilot plant (Zinsly et al, 2001) and with a Comm.a-La (Matsumoto et al, 2001) demonstrated that whey proteins were capable of inhibiting the development of ulcerative lesions in the rat stomach mucosa by various ulcerogenic agents. Rosaneli et al (2004) used the same WPC, which was used in the present work to isolate a-La, and reported a 50% decrease of the ULI when two consecutive daily doses of 1000 mg kg À1 bw were administered to the rat, in the indomethacin model.…”
Section: Article In Pressmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies reported recently (Rosaneli, Bighetti, Antoˆnio, Carvalho, & Sgarbieri, 2002, 2004) with a WPC produced in a pilot plant (Zinsly et al, 2001) and with a Comm.a-La (Matsumoto et al, 2001) demonstrated that whey proteins were capable of inhibiting the development of ulcerative lesions in the rat stomach mucosa by various ulcerogenic agents. Rosaneli et al (2004) used the same WPC, which was used in the present work to isolate a-La, and reported a 50% decrease of the ULI when two consecutive daily doses of 1000 mg kg À1 bw were administered to the rat, in the indomethacin model.…”
Section: Article In Pressmentioning
confidence: 99%
“…Rosaneli et al (2004) used the same WPC, which was used in the present work to isolate a-La, and reported a 50% decrease of the ULI when two consecutive daily doses of 1000 mg kg À1 bw were administered to the rat, in the indomethacin model. If one considers a-La as the only active compound in WPC against ulcerative lesions caused by indomethacin and an average concentration of 20% aLa in the WPC, then the 50% lowering in ULI by a 1000 mg dosage of WPC is perfectly coherent with the 12% decrease by 200 mg kg À1 bw of a-La used in the present study.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Whey proteins as α-lactalbumin would also have gastroprotector effect (Matsumoto et. al., 2001;Rosaneli et. al., 2004;Ushida et.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Whey proteins have been reported to lower blood cholesterol (JACOBUCCI et al, 2001) and protect gastric mucosa against ulcerogenic drugs (ROSANELI et al, 2002;ROSANELI et al, 2004;MEZZAROBA et al, 2006).…”
Section: Introductionmentioning
confidence: 99%